2020
DOI: 10.3390/bs10060099
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Close Relationships and Loss of Religious Belonging as Cumulative Ostracism: From Social Death to Social Resurrection

Abstract: Background: Ostracism is a negative experience that has been studied primarily in laboratory settings. This study extends current research by investigating ostracism in daily life, analyzing the transition from social death to social resurrection of Catholic partners who suffered ostracism both in the couple (with the consequent divorce) and in the religious community they belong to (ban from religious practices). Therefore, we introduce the notion of ‘cumulative ostracism’. Method: Data are composed of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Though religiosity can greatly assist those who endure the pain of loss and trauma ( 63 , 102 ), in this case, the pain embodies an additional trauma—that is, feeling rejected by the religion to which one is devoted. As evidenced in the literature, this experience is similar to that of divorced Catholic individuals ( 103 ) and of Jehovah's Witnesses who broke away from their original group ( 104 ). All of these religious people suffer from cumulative ostracism which generates great psychological distress because of a series of rapid losses.…”
Section: Discussionsupporting
confidence: 58%
“…Though religiosity can greatly assist those who endure the pain of loss and trauma ( 63 , 102 ), in this case, the pain embodies an additional trauma—that is, feeling rejected by the religion to which one is devoted. As evidenced in the literature, this experience is similar to that of divorced Catholic individuals ( 103 ) and of Jehovah's Witnesses who broke away from their original group ( 104 ). All of these religious people suffer from cumulative ostracism which generates great psychological distress because of a series of rapid losses.…”
Section: Discussionsupporting
confidence: 58%
“…Since social exclusion is an experience in which excluders can direct and control the interaction as they desire, the excluded individual's sense of control is diminished (Zamperini et al., 2020). To cope with this situation, the excluded individuals may adopt an accusing and aggressive attitude and be inclined to negative or anti‐social behaviours to express that they have regained a sense of control (Williams, 2009; Williams & Nida, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Moreover, the model of ostracism does not consider romantic relationship dissolution, romantic rejection, or self-protection from harassment as possible antecedents and/or inferred motives. Finally, our study does not allow us to support similarities between long-term effects of ghosting and the third phase of the Temporal Need Threat-Model, though some participants suggested that being repeatedly ghosted from various potential partners could have a cumulative effect on one's self-esteem, in a similar way to cumulative experiences of ostracism (Zamperini et al, 2020).…”
Section: Discussionmentioning
confidence: 72%